Effect of Ovirich® on Blood Chemistry in White Leghorn Layer - Vinod Garjola. Anshu Rahal; Ripusudan Kumar; B.C. Mondal; Meena Mrigesh (Archives of Current Research International, 2025)
Ovirich® is a phytogenic molecules-yeast-mineral formulation used in poultry but still its effect on haematobiochemical parameters is unknown. Present experiment was conducted to discern the effect of Ovirich® in White Leghorn birds (90 in numbers; 22 weeks age) which were divided into three treatment groups using completely randomized design (CRD). The control group (T1) received the basal diet without any supplementation, while in treatment groups T2 and T3; the basal diet was supplemented with 0.75 kg and 1.0 kg of supplement per ton of basal feed, respectively. Blood chemistry was assessed at the end of feeding trial at 34 week age of birds. Significant differences (P≤0.05) were observed in haemoglobin, PCV, TEC, TLC, MCV, MCH, MCHC, SGPT, SGOT, total protein, albumin, globulin, glucose, total cholesterol, triglycerides, serum calcium and phosphorus in supplemented groups. It was concluded that Ovirich® in the basal diet can affect blood biochemistry in White Leghorn layers.